Biocompatible multifunctional lubricating oil additives. (2nd August 2016) - Ghosh, P.; Das, M.
ABSTRACT: Six copolymers of different concentration of dodecyl acrylate and 1-decene with sunflower oil were prepared and their characterization was carried out by spectral, thermogravimetric, and viscometric analysis. Performance evaluation indicates that the polymers effectively act as pour point depressant and viscosity modifier. The viscosity index and pour point values depend on the nature of mineral base oils, polymer type, and also on the concentration of the additives in solution. Biodegradability test was also carried out and as anticipated, the sunflower oil copolymers showed a biodegradable nature in the additive.